Dampak Kompetensi Key user ERP terhadap Kinerja Inovasi dan Kinerja Kualitas Guna Meningkatkan Kinerja Organisasi - Zeplin Jiwa Husada Tarigan; Sautma Roni Basana (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Implementation EntERPrise Resource Planning (ERP) requires user key to have a reliable competency especially in personnel management. For this study, a survey was conducted using interviews technique and distributing questionnaires to 80 manufacturing industry practitioners, with response rate 88.75%. Additionally, the data analysis was done using PLS with Jawa Web Start program. The findings of the research are: There is no influence between knowledge and skill in quality performance and innovation performance in improving the performance of the company while implementing the technology of ERP. Personality Characteristics affect the increase of quality performance and innovation in the improvement of the company's performance while implementing ERP technology. Demonstrable Performance effect the increase in the quality of performance and innovation in improving the company's performance while implementing ERP technology. Innovation performance and Quality performance together have a direct impact on enhancing the performance of companies while implementing ERP technology.